MIGRATION OF BIOMICROELEMENTS IN CLAYEY SOILS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article provides a theoretical analysis of the differential biogeochemical migration of biomicroelements in contaminated soils and the biosphere. It emphasizes the crucial role of biomicroelements in the exchange of substances between living and nonliving matter.